Drawn to the special attention of the House : Central Counterparties (Transitional Provision) (Extension and Amendment) Regulations 2022 ; Education (School Teachers' Qualifications and Induction Arrangements) (Amendment) (England) Regulations 2022 ; Communications Act 2003 (Restrictions on the Advertising of Less Healthy Food) (Effective Date) (Amendment) Regulations 2022 : 24th Report of Session 2022-23 /: Central Counterparties (Transitional Provision) (Extension and Amendment) Regulations 2022 ; Education (School Teachers' Qualifications and Induction Arrangements) (Amendment) (England) Regulations 2022 ; Communications Act 2003 (Restrictions on the Advertising of Less Healthy Food) (Effective Date) (Amendment) Regulations 2022 : 24th Report of Session 2022-23. ([2022-12-22]) - Unknown
No abstract available